2005
DOI: 10.1128/jb.187.15.5122-5128.2005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ExsFA and ExsFB Proteins to the Localization of BclA on the Spore Surface and to the Stability of the Bacillus anthracis Exosporium

Abstract: Spores of Bacillus anthracis, the etiological agent of anthrax, and the closely related species Bacillus cereus and Bacillus thuringiensis, possess an exosporium, which is the outermost structure surrounding the mature spore. It consists of a paracrystalline basal layer and a hair-like outer layer. To date, the structural contribution of only one exosporium component, the collagen-like glycoprotein BclA, has been described. It is the structural component of the hair-like filaments. Here, we describe two other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 44 publications
7
127
0
Order By: Relevance
“…2c, d), although other spore antigens were also recognized ( Fig. 2f) (Steichen et al, 2003(Steichen et al, , 2005Sylvestre et al, 2002Sylvestre et al, , 2005. We observed that bclA : : Kan spores were also not significantly opsonized by anti-spore IgG when compared to wild-type Ames strain spores (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…2c, d), although other spore antigens were also recognized ( Fig. 2f) (Steichen et al, 2003(Steichen et al, , 2005Sylvestre et al, 2002Sylvestre et al, , 2005. We observed that bclA : : Kan spores were also not significantly opsonized by anti-spore IgG when compared to wild-type Ames strain spores (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…B. anthracis was grown in BHI broth (Becton Dickson, MD) supplemented with 0.5% glycerol at 37°C unless otherwise noted. Spores were produced by plating on NBY media with antibiotics when necessary and incubated at 30°C for 10 days, then harvested and purified on an Omnipaq gradient (350 milligrams of iodine/mL) (GE Healthcare, NJ), similar to previously described methods [81,261,289]. Escherichia coli strains were either α-select (Bioline, MA) or dcm, dam-deficient GM119 (dcm-6, dam-3) [290] and grown in LB broth with appropriate antibiotics when necessary (Becton Dickson, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Omnipaq gradient (350 milligrams of iodine/mL), similar to previously described methods [81,261,289]. The E.coli strains used were either α-select (Bioline, MA) or dcm, dam-deficient GM119…”
Section: Bacterial Strains and Animalsmentioning
confidence: 99%
See 2 more Smart Citations